2019
DOI: 10.3389/fpsyg.2019.02263
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Emotion-Related Processes in Classroom Activities Through Functional Measurements

Abstract: To improve educational research focusing on such complex phenomenon as the interaction of emotion-related processes (affects) and students’ learning classroom activities, the collaboration between educational studies and neurosciences appears particularly relevant. Stress or “stress response” being an emotion-related psychological process (Gross, 2015) and having a neurobiological origin (Selye, 1956) is mostly studied in neurophysiological research using laboratory controlled objective measurements. One of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…Blood and heart rates and oxygen saturation were the signs of (response to) stress analyzed in this study. These are possibly the main biological expressions investigated in neurophysiological studies (Prokofieva, Kostromina, Polevaia, & Fenouillet, 2019). The present study found especial outcomes in the systolic blood rate and oxygen saturationthat were statistically significantly different between females and males.…”
Section: Discussionsupporting
confidence: 49%
“…Blood and heart rates and oxygen saturation were the signs of (response to) stress analyzed in this study. These are possibly the main biological expressions investigated in neurophysiological studies (Prokofieva, Kostromina, Polevaia, & Fenouillet, 2019). The present study found especial outcomes in the systolic blood rate and oxygen saturationthat were statistically significantly different between females and males.…”
Section: Discussionsupporting
confidence: 49%
“…Emotion-related processes strongly influence emotional stated such as anxiety and depression, but also mental, behavioral and physical health of the individual (Lumley et al, 2011). There are consistent literature data in cognitive sciences that highlighted the importance of affective state and emotions in learning (Baker et al, 2010;Prokofieva et al, 2019;Woolf et al, 2009). Yet, learning and memory are strongly involved in psychopathology of chronic pain and some authors suggest that "chronic pain is pain that does not extinguish its memory trace" (Mansour et al, 2014).…”
Section: Introductionmentioning
confidence: 88%
“…Stress response was measured by changing cardiovascular parameters of HRV (Polevaia et al, 2016; Polevaia, Parin, Polevaia, & Demareva, 2017; Prokofieva et al, 2019). The telemetric wireless ECG was registered in 24 students ( N = 24) while they were doing the same activity as the other students of the class.…”
Section: Methodsmentioning
confidence: 99%
“…The periods of stress response referred to the following pattern: a simultaneous decrease of a TP of the heart rate and an increase of parasympathetic index ( LF/HF ) corresponding to the sympathetic activation and the parasympathetic withdrawal (Berntson, Quigley, Norman, & Lozano, 2016; Prokofieva et al, 2019).…”
Section: Methodsmentioning
confidence: 99%